The Effect of Family Empowerement in Preventing Stunting: Systematic Literature Review - Suprihatin Suprihatin; Runjati Runjati; Arwani Arwani (Indonesian Journal of Global Health Research, 2024)
Stunting is chronic malnutrition which is based on an index of body length compared to age (PB/U) or height compared to age (TB/U) with a limit (z-score) of less than -2 SD (Standard Deviation). Stunting problems need to be detected early, so that the interventions given can reduce long-term effects. Detection and management of stunting is carried out through empowerment efforts. Family empowerment as an effective step to reduce stunting cases through prevention and management efforts. The role of parents is very important in preventing stunting through detection and management. Anthropometric-based instruments that are easy to use are needed for the detection and management of stunting. Objective to analyze the variety of health promotion strategies to prevent stunting. The research design is a Systematic Literature Review of articles or journals published in 2018-2023, accessed on Google Scholar, PubMed and Scopus with the Prisma Flow technique. Research with different designs ranging from descriptive studies to quasi-experimental and participatory studies shows that an integrated and family-based approach can significantly improve knowledge, skills and awareness about stunting prevention. Programs involving education on exclusive breastfeeding, healthy food processing for toddlers, and maternal reproductive health have proven effective in reducing the prevalence of stunting. Health promotion strategies found in the literature review were mostly conceptual rather than operational and did not show when these strategies successfully reduced stunting.